Evaluation of Serum Cytokines Biomakers in HIV-Infected Subjects Before and After Commencement of Haart in Federal Teaching Hospital Gombe - Abubakar, S.,; Ibeh, Nancy, (British Journal of Healthcare and Medical Research, 2023)
The Human Immunodeficiency Virus (HIV) infection causes the acquired immunodeficiency syndrome (AIDS), which is a systemic disorder characterized by severe impairment and progressive damage of both cellular and humoral immune responses. The aim of this study is to evaluate the effect of long administration of HAART on haematological indices, immunological biomarkers, Biochemical and some cytokines in HIV infected subjects at federal teaching hospital Gombe. This is a cross sectional study carried out from May to December 2021 on 132 HIV infected adults. The design entails collecting pre and post blood sample after treatment with highly anti-retroviral treatment (HAART) for more than six months. Out of the 132 subjects studied, 66 were HIV sero-positive and these were the test group, while the remaining 66 were HIV Sero-negative drawn from client visiting blood bank of FTH Gombe to make voluntary donation and HIV Testing Unit (HTS) for Marital and Medical Certificate of Fitness Screening and served as control group. All the subjects were between the ages of 15 - 65 years and are aged matched with the control group. Demographic data was collected using structured questionnaire. The protocol entails collecting 9mls of venous blood from those who were seropositive for HIV 1 &2 before commencement of HAART. This sample is designed pre- treatment sample and these individuals were followed up for 6 months and a second sample collection was done some were lost to follow up and so the attrition was compensated by also collecting blood samples from other HIV individual who had been on HAART for several years. 4ml was dispensed into EDTA bottle for Full blood count using ELIZA analyzer. P<0.05 was considered as significant.The result of the analysis indicated that the mean±se of Interleukines-2 (IL-2) (pg/ml) and Interleukines -6 (IL-6) (pg/ml) parameters for the control group are 65.43 ± 3.37and 34.74 ± 1.20 respectively. The mean±se of the treatment naïve for IL-2 and IL-6 are 101.61 ± 16.47 and 14.63 ± 1.65 respectively. Also, the mean±se of the treatment/HAART for Interleukines-2 (IL-2) (pg/ml) and Interleukines -6 (IL-6) (pg/ml) are 67.43 ± 1.40 and 10.80 ± 0.45 respectively. The IL-2 significantly higher among treatment Naïve HIV infected participants when compared with treatment and control group with (p-value < 0.05). The result is also shown in table 2.0 Above.From this work it is clear that all the cases in this regard, confirm the fact that Long-term HAART remarkably drops the viral load and inflammation in HIV positive subjects and shows that a low-level inflammation continues which probably leads to chronic inflammatory state, morbidity and mortality in this group of subjects among HIV positive patients in this part of Northern Nigeria despite the reported side effects